2020
DOI: 10.1186/s13195-020-00689-0
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of CSF core Alzheimer disease biomarkers for routine clinical diagnosis: do fresh vs frozen samples differ?

Abstract: Background Cerebrospinal fluid (CSF) amyloid-beta (Aβ) 42/40 ratio, threonine-181-phosphorylated-tau (p-tau), and total-tau (t-tau) represent core biomarkers of Alzheimer disease (AD). The recent availability of automated platforms has represented a significant achievement for reducing the pre-analytical variability of these determinations in clinical setting. With respect to classical manual ELISAs, these platforms give us also the possibility to measure any single sample and to get the result within approxim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…In SAD, the ApoE4 ( Konttinen et al, 2019a ) and TREM2 ( Kleinberger et al, 2014 ) mutations have been associated with reduced phagocytosis by immune cells, which could be involved in the EV increase seen in AD. Additionally, a recent study found altered EV biogenesis and autophagy impairment (failure to include LAMP-1 in lysosomes) in preclinical models and clinical AD patients ( Gallart-Palau et al, 2020 ), which could be associated with the EV-brain size and count increase seen in AD. Autophagy markers should therefore be further evaluated in systemic EVs to better clarify this association.…”
Section: Discussionmentioning
confidence: 99%
“…In SAD, the ApoE4 ( Konttinen et al, 2019a ) and TREM2 ( Kleinberger et al, 2014 ) mutations have been associated with reduced phagocytosis by immune cells, which could be involved in the EV increase seen in AD. Additionally, a recent study found altered EV biogenesis and autophagy impairment (failure to include LAMP-1 in lysosomes) in preclinical models and clinical AD patients ( Gallart-Palau et al, 2020 ), which could be associated with the EV-brain size and count increase seen in AD. Autophagy markers should therefore be further evaluated in systemic EVs to better clarify this association.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the known non-optimal normality of biomarker data ( Bellomo et al, 2020a ), Passing Bablok regressions ( Passing and Bablok, 1983 ) were preferred to parametric least squares regressions. Confidence intervals (CI) for the fitted parameters were calculated with the bootstrap method ( Carpenter and Bithell, 2000 ).…”
Section: Methodsmentioning
confidence: 99%
“…Studies showed that AD proteins remain intact in the CSF for about 12 years, but beyond that, protein levels may change. [47][48][49] Despite the sampling time, we found a good expression of miR-502-3p and miR-501-3p in the same samples. This longevity could be an advantage of miRNA as a biomarker over traditional protein biomarkers.…”
Section: Discussionmentioning
confidence: 98%